55.5k views
4 votes
F(x) = 3x-1 , (f of g)(x) = x^2 , Find g(x)

User Spankymac
by
5.7k points

1 Answer

5 votes

Answer:


g(x)=(x^2+1)/(3)

Explanation:

Given functions:


\begin{cases}f(x)=3x-1\\(f \circ g)(x)=x^2\end{cases}

Composite functions are when the output of one function is used as the input of another.

Therefore, the given composite function (f o g)(x) means to substitute function g(x) in place of the x in function f(x).


\begin{aligned}(f \circ g)(x) & = x^2\\f(g(x)) & = x^2\\\implies 3(g(x))-1 & = x^2\\3(g(x))-1+1 & = x^2+1\\3(g(x))&=x^2+1\\(3(g(x)))/(3)&=(x^2+1)/(3)\\\implies g(x)&=(x^2+1)/(3)\end{aligned}

Therefore:


\boxed{g(x)=(x^2+1)/(3)}

User Sergey Emeliyanov
by
6.3k points